Desain Aplikasi MindSpare sebagai Media Literasi dan Dukungan Kesehatan Mental dengan Metode Design Thinking - Asa Prameswari Karso; I Gede Surya Rahayuda (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
Mental health is a global issue that needs attention, especially for adolescents aged 16-24 years. Previous research shows that the mental health of adolescents of this age affects how their well-being is. Then, based on preliminary research that has been conducted on adolescents of that age, 83% of respondents have never used a mental health application with one of the reasons is that they feel they don't need the application. Therefore, in this study, a mental health application design was made as a medium of support for someone experiencing mental health problems and as a literacy medium for someone who is mentally healthy to be more aware of the surrounding environment. This research process is carried out using the Design Thinking method so that the application built can meet user needs. The design that has been made is tested using the UEQ scale and most aspects shows Excellent rating, with the highest score in the Attractiveness aspect, with an average value of 2.29.